If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + -3)(3x + 9) = 0 Reorder the terms: (-3 + 2x)(3x + 9) = 0 Reorder the terms: (-3 + 2x)(9 + 3x) = 0 Multiply (-3 + 2x) * (9 + 3x) (-3(9 + 3x) + 2x * (9 + 3x)) = 0 ((9 * -3 + 3x * -3) + 2x * (9 + 3x)) = 0 ((-27 + -9x) + 2x * (9 + 3x)) = 0 (-27 + -9x + (9 * 2x + 3x * 2x)) = 0 (-27 + -9x + (18x + 6x2)) = 0 Combine like terms: -9x + 18x = 9x (-27 + 9x + 6x2) = 0 Solving -27 + 9x + 6x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '3'. 3(-9 + 3x + 2x2) = 0 Factor a trinomial. 3((-3 + -1x)(3 + -2x)) = 0 Ignore the factor 3.Subproblem 1
Set the factor '(-3 + -1x)' equal to zero and attempt to solve: Simplifying -3 + -1x = 0 Solving -3 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -1x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -1x = 0 + 3 -1x = 0 + 3 Combine like terms: 0 + 3 = 3 -1x = 3 Divide each side by '-1'. x = -3 Simplifying x = -3Subproblem 2
Set the factor '(3 + -2x)' equal to zero and attempt to solve: Simplifying 3 + -2x = 0 Solving 3 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -2x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -2x = 0 + -3 -2x = 0 + -3 Combine like terms: 0 + -3 = -3 -2x = -3 Divide each side by '-2'. x = 1.5 Simplifying x = 1.5Solution
x = {-3, 1.5}
| 9(t-2)+3t=6(2t+4)-9 | | 2x=12x^2+2x | | 2x^3+20x^2+48=0 | | 7y+x=26 | | 16x-3+3x-5=-3x-63 | | 5(9x+4)=290 | | (300-x)100=110 | | 4(3n+4)=2(6n+8) | | y-9x=22 | | 8(10x-9)=488 | | X=11y-4 | | 12/36=4/c | | 0.85x+.05(10-x)=.10(-107) | | 11y-4=x | | 10/12=b/6 | | -4x(4x-1)=0 | | (-4.2x^4)(3x^7)= | | 7/y=49/98 | | 92-y=x | | y=7500-9.5(8000) | | y=7500-9.5(10000) | | 25m=75 | | y=75000+9.5x | | 27+8=10 | | 4(C-9)C=15 | | 31=p-91 | | k*k=36 | | 40*2=r | | 3x-3=1+2x | | x*-10(x-1)=-11 | | 3x-3=9-6x | | 9x^2+3x-50=0 |